Dietary intake of elite figure skating dancers - Ziegler, P. J.; Jonnalagadda, S. S.; Lawrence, C. (2001)
The main objective of the present study was to examine the dietary intake and physiological status of members of the US National Figure Skating Dance Team. Study participants included seven female and seven male figure skating dance pairs. Three-day food records were collected from each dancer and analyzed using a computerized nutrient database. Height, body weight and skinfold measurements were completed on each dancer. Body fat was estimated using the Jackson et al prediction equations. Fasting blood samples were collected for biochemical analysis. Total energy intake of female dancers (1416 kcal/d, 339 kjoules/day) was considerably lower than the dietary recommendations, while the male dancers appeared to have adequate energy intake (2837 kcal/d, 679 kjoules/day). Carbohydrate intake of both male and female dancers was below the recommendations, 44% and 51%, respectively, whereas total fat and protein intake of both male and female dancers were higher than the dietary recommendations. All dancers met at least 2/3(rd) of the dietary recommendations for all micro-nutrients, except folate and zinc intake of the female dancers, which were 68% and 62% of the recommended values. Although, blood lipid concentrations and other physiological parameters of the overall group were within normal ranges, two of the dancers (14% of the dancers) had elevated blood cholesterol concentrations and low iron status. The results of the present study suggest that these elite figure skating dancers, especially females, may not be consuming adequate amounts of energy-yielding nutrients and those that influence bone health. Future studies are needed to examine the effects of nutritional status on performance of these figure skating dancers and to develop strategies to improve the nutritional status of these elite dancers. Nutr Res 2001 Jul;21(7):983-992